Spatial and Temporal Intensity of HFMD Cases in Pulau Pinang, Malaysia between 2017 and 2022 - Hamedin, Mohamad Afiq Amsyar; Musa, Kamarul Imran; M Fathil, Noor Farhana; M Shah, Rozaini (IIUM Medical Journal Malaysia, 2025)
Introduction: Hand, foot and mouth disease (HFMD) remains a significant public health concern in Malaysia, persisting despite existing control measures. This study aimed to assess the spatial and temporal dynamics of HFMD in Pulau Pinang, a north-western state of Malaysia. Materials and methods: Data were retrieved from the Communicable Diseases Control Information System (CDCIS) E-Notification Version 2011, including all notified HFMD cases in Pulau Pinang from 2017 to 2022. The number of cases by district was estimated using the points-in-polygons function in the sf package in RStudio. Kernel Density Estimates (KDE) were used to assess spatial intensity, while spatial clustering was evaluated using the nearest neighbor index (NNI). Results: A total of 15 586 notified HFMD cases reported in Pulau Pinang between 2017-2022. Temporally, the spatial intensity of cases fluctuated, with a peak in 2018, followed by a marked decline in 2020 and 2021 and a resurgence in 2022. Spatially, the highest intensity of infections was consistently observed in the district of Timur Laut, particularly in urban subdistricts such as Bandar Georgetown and Mukim 13 (Paya Terubong). Over time, high-intensity areas expanded to include Barat Daya and parts of Seberang Perai, including Mukim 12 (Bayan Lepas) and central areas of Seberang Perai Tengah, Utara, and Selatan. Evidence of significant spatial clustering was detected across all years based on nearest neighbor index values (NNI: 0.21–0.50). Conclusion: HFMD cases in Pulau Pinang showed marked spatial clustering and shifting intensity patterns, especially in densely populated and newly developed areas. These findings highlighted the need for targeted, locality-specific prevention strategies to curb HFMD transmission.